2021
DOI: 10.1093/mnras/stab820
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fundamental jet properties with multiwavelength fast timing of the black hole X-ray binary MAXI J1820+070

Abstract: We present multi-wavelength fast timing observations of the black hole X-ray binary MAXI J1820+070 (ASASSN-18ey), taken with the Karl G. Jansky Very Large Array (VLA), Atacama Large Millimeter/Sub-Millimeter Array (ALMA), Very Large Telescope (VLT), New Technology Telescope (NTT), Neutron Star Interior Composition Explorer (NICER), and XMM-Newton. Our data set simultaneously samples ten different electromagnetic bands (radio – X-ray) over a 7-hour period during the hard state of the 2018–2019 outburst. The emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 93 publications
(106 reference statements)
4
45
0
Order By: Relevance
“…Recently, X-ray spectral timing-analysis of the BHXB MAXI J1820 + 070 also suggest a similar picture by finding an increasing coronal height towards the HIMS-to-SIMS state transition (Wang et al 2021;De Marco et al 2021) (with the caveat that a similar trend is not found in the time-averaged X-ray spectrum). Additionally, based on multi-wavelength variability, Tetarenko et al (2021) also tentatively propose that the jet bulk Lorenz factor may be an increasing function of the bolometric luminosity, and Wood et al (2021) find evidence of an increasing ejecta speed of jet blobs as transition nears. Either mechanism is consistent with a model in which the accretion flow gets progressively more magnetically dominated (up to the so-called magnetically arrested disc, or MAD, state) as the accretion rate increases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, X-ray spectral timing-analysis of the BHXB MAXI J1820 + 070 also suggest a similar picture by finding an increasing coronal height towards the HIMS-to-SIMS state transition (Wang et al 2021;De Marco et al 2021) (with the caveat that a similar trend is not found in the time-averaged X-ray spectrum). Additionally, based on multi-wavelength variability, Tetarenko et al (2021) also tentatively propose that the jet bulk Lorenz factor may be an increasing function of the bolometric luminosity, and Wood et al (2021) find evidence of an increasing ejecta speed of jet blobs as transition nears. Either mechanism is consistent with a model in which the accretion flow gets progressively more magnetically dominated (up to the so-called magnetically arrested disc, or MAD, state) as the accretion rate increases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The emission at different wavebands correlates with each other, with time-lags ranging from hundreds of milliseconds between the X-ray/optical bands to minutes between the radio/sub-mm bands [7]. The derived magnetic field from model fitting is about 10 4 Gauss in the jet base region [7]. The well-known microquasars SS433 and GRS 1915+105 also demonstrated relativistic jets with the large jet-viewing angles with respect to our line of sight.…”
Section: The Radio Emission Of Bhxbmentioning
confidence: 64%
“…Below, we briefly summarize the radio properties of BHXBs according to their radio phases from flare/outburst state to quiescent state. In the flare state, for example, a highly relativistic and confined (∼0.5 • ) jet is observed in MAXI J1820+070, which carries a significant amount of power away from the system (equivalent to 0.6 × L 1-100 keV ) [7]. The jet shows a large bulk Lorenz factor of 6.8 with a high Eddington ratio of ∼0.1, and its total radio/sub-mm flux density peaks at roughly >1000 GHz [7,8].…”
Section: The Radio Emission Of Bhxbmentioning
confidence: 99%
See 2 more Smart Citations